TEACHER COLLABORATION AND STUDENT ACHIEVEMENT OF PUBLIC ELEMENTARY SCHOOLS IN THE SCHOOLS DIVISION OF ROXAS CITY - Artillero, Marylou Belsvis (President University, 2025)
This study examined the perceptions of teacher collaboration and student achievement among 119 public elementary school teachers in District 1 of Roxas City Division for the academic year 2023-2024. The intent was to analyze the interrelation between teachers' collaborative efforts and student success in the educational setting. This descriptive-correlational designed study utilized a validated and reliability-tested, researcher-made questionnaire. The research stands out by providing empirical evidence from a specific educational district, thus enriching the body of knowledge concerning teacher interactions and their direct impact on student performance. The findings of this study underscored a very satisfactory level of teachers' collaboration alongside a satisfactory level of student achievement. Interestingly, no significant differences were noted in the degree of teachers' collaboration or students' achievement when respondents were categorized by sex, age, length of service, or grade level taught. Moreover, a significant positive correlation was identified between the degree of teachers' collaboration and the level of students' achievement. Based on these findings, it is recommended that educational policy and practice continue to support and enhance teacher collaboration as a lever for raising student achievement. The absence of significant differences across demographic groups suggests that collaborative practices are universally beneficial and should be encouraged across the board. Further research could explore the causal nature of this relationship and identify specific collaborative practices that are most effective in improving student outcomes.